2017
DOI: 10.17488/rmib.38.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Automatic movement segmentation in the upper limb functional assessment of children with cerebral palsy

Abstract: Cerebral Palsy (CP) is a group of permanent pre, post and perinatal disorders of the motor and posture development due to non-progressive alterations in brain’s natural development caused by injuries in the Central Nervous System. Due to the importance of the daily use of the upper limb members, it’s important to consider more efficient ways to evaluate the performance in patients diagnosed with CP. One way to obtain an evaluation of the performance of the thoracic member is recording defined movements and cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The results of Anaya et al [ 61 ] indicated that the smoothness metric is an efficient measure of the upper limb movement that can be used to determine the differences between an affected and an unaffected limb. They are currently investigating the correlation of the results obtained with clinical scales and are developing an objective scale for a functional assessment based on SALM smoothness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of Anaya et al [ 61 ] indicated that the smoothness metric is an efficient measure of the upper limb movement that can be used to determine the differences between an affected and an unaffected limb. They are currently investigating the correlation of the results obtained with clinical scales and are developing an objective scale for a functional assessment based on SALM smoothness.…”
Section: Discussionmentioning
confidence: 99%
“…However, the analysis requires sending patients to a clinical laboratory and is most commonly used to assess kinematics and spatiotemporal variables during activities such as reaching and grasping [ 55 , 56 , 57 , 59 , 62 , 64 , 66 ]. Wearable inertial sensors also directly measure kinematic data of the human body and are an alternative able to be used both in the laboratory and in an open environment [ 61 , 63 , 67 ]. Another less expensive alternative with more advantages is the use of Kinect devices (Microsoft, Redmond, WA, USA) [ 60 , 65 ].…”
Section: Current Techniques For Objective Measurementsmentioning
confidence: 99%
See 2 more Smart Citations